Relationship between welding conditions and the mechanical properties of welded aluminium structures - Tan, Joseph (Universiti Malaysia Sarawak, (UNIMAS), 2001)
This research describes the relationships between welding conditions and the mechanical properties of welded aluminium structures. It also subsequently derives several relationships in order to determine the objectives of the research. There were two objectives of this research: to investigate the relationships between welding process and the mechanical properties of welding aluminium components. Besides, it is also investigate effects of pre and post weld treatment on the mechanical properties. From the investigation, we can determine the correlations of this project.